Tropolone-induced effects on the unfolded protein response pathway and apoptosis in multiple myeloma cells are dependent on iron. (February 2019) - Haney, Staci L.; Varney, Michelle L.; Safranek, Hannah R.; Chhonker, Yashpal S.; G-Dayanandan, Narendran; Talmon, Geoffrey; Murry, Daryl J.; Wiemer, Andrew J.; Wright, Dennis L.; Holstein, Sarah A.
Highlights: Iron prevents induction of myeloma cell death by the novel tropolone MO-OH-Nap. Iron prevents MO-OH-Nap induction of the unfolded protein response (UPR) pathway. The iron chelator deferoxamine induces upregulation of the UPR in myeloma cells. MO-OH-Nap directly chelates iron and upregulates transferrin receptor expression. Abstract: Tropolones are naturally occurring seven-membered non-benzenoid aromatic compounds that are of interest due to their cytotoxic properties. MO-OH-Nap is a novel α-substituted tropolone that induces caspase cleavage and upregulates markers associated with the unfolded protein response (UPR) in multiple myeloma (MM) cells. Given previous reports that tropolones may function as iron chelators, we investigated the effects of MO-OH-Nap, as well as the known iron chelator deferoxamine (DFO), in MM cells in the presence or absence of supplemental iron. The ability of MO-OH-Nap to induce apoptosis and upregulate markers of the UPR could be completely prevented by co-incubation with either ferric chloride or ammonium ferrous sulfate. Iron also completely prevented the decrease in BrdU incorporation induced by either DFO or MO-OH-Nap. Ferrozine assays demonstrated that MO-OH-Nap directly chelates iron. Furthermore, MO-OH-Nap upregulates cell surface expression and mRNA levels of transferrin receptor. In vivo studies demonstrate increased Prussian blue staining in hepatosplenic macrophages in MO-OH-Nap-treated mice. These studies demonstrate that MO-OH-Nap-induced cytotoxic effects in MM cells are dependent on the tropolone's ability to alter cellular iron availability and establish new connections between iron homeostasis and the UPR in MM.